Development of a low-cost and portable device controller for point-of-care medical diagnostics - Jahanshahi, P.; Md Dawal, S.Z.; Ibrahim, F.; Nozari, A.A.; Soin, N. (2010)
The field of centrifugal microfluidics aims to miniaturize common biochemical assays onto specialized discs (CDs). By the exploitation of the centrifugal force, centrifugal microfluidics CDs do not require the syringe pumps that stationary microfluidic platforms require. This paper describes the development of a low-cost and portable controller device that is capable of performing centrifugal microfluidics at the point-of-care (POC). Overall, this system aims to be low in cost, fast, and modular. In this study, the Spin-Stand device controller is the final product of three stages of development: design, virtual simulation and implementation. At the core of the system, the controller is designed to adjust the disc rotational speed for performing several operations by Pulse Width Modulation (PWM) through PIC (Programmable Interface Controller). Â© 2010 IEEE.